Các yếu tố ảnh hưởng đến ý định mua lại trực tuyến: Trường hợp nghiên cứu trên địa bàn Thành phố Hồ Chí Minh - Trần Thị Thu, Hiền; Nguyễn Thị, Bình; Nguyễn Minh, Hiếu (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
This study aims to explore the factors affecting the online repurchase intention of people living in Ho Chi Minh City through an extended version of the Technology Acceptance Model (TAM). By employing the Partial Least Squares Structural Equation Modeling (PLS-SEM) method on a sample of 610 observations, the results reveal that there are four factors influencing the online repurchase intention of people living in Ho Chi Minh City including (1) attitudes toward online shopping, (2) perceived usefulness, (3) perceived ease of use, and (4) environmental awareness. Among these factors, attitude is the strongest predictor of the repurchase intention and also mediates the relationship between other independent variables and the repurchase intention. Notably, perceived risks of online shopping and personalization did not affect the repurchase intention. From the above findings, some implications for online businesses to enhance the customers’ intention to continue shopping online are suggested.
Keywords: Online Shopping; Perceived Risks of Online Shopping; TAM; Ho Chi Minh City; Personalization; Online Repurchase Intention